Perbandingan Nilai Akuntansi Jasa Dagang dan Pengantar Akuntansi 1 pada Dua Kurikulum Berbeda. Studi Kasus: Program Studi Akuntansi Vokasi UI - Birawani Dwi Anggraeni; Yulial Hikmah; Sandra Aulia Zanny (Pusat P2M Politeknik Negeri Batam, 2017)
Accounting Studies Vocational UI begin implementing a new curriculum based on competency started the school year 2016/2017. The curriculum changes implemented in the 2016 freshmen class accounting curriculum change significantly in terms of both depth and breadth of study material, naming the subjects or the number of hours of study implementation. The purpose of this study to compare the final value accounting students in the subject of Accounting Services trade on the New Curriculum and course Introduction to Accounting 1 Curriculum Lama where the subject is given in the first semester as a basic accounting course. The data used in this study is the student of 2016 and 2015. The methodology used is two different hypothesis test average. Limitations of this study was to use secondary data that the final value to be tested with a significance test average of two independent. Results obtained from this research possible differences in learning achievement results are reflected in the final grades of students using the new curriculum. New curriculum in 2016 is considered to provide a significant effect on students' academic achievement in basic accounting course, as a foundation reinforcement materials accounting for the next semester.